Nutritional Content Analysis of Tofu Waste in Catfish (Pangasionodon hypophthalmus) Farmer Tangkit Baru Jambi - Bs Monica Arfiana; Sarwo Edy Wibowo; Wulandari Wulandari; Dyah Muji Rahayu; Yatno Yatno (Sriwijaya Journal of Environment, 2022)
One of the factors behind the declining catfish farm in Tangkit Baru, Jambi, is the rising price of commercial feed. A lot of fish farmers stop their cultivation. They make independent feed formulations based on existing sources around them. The lack of knowledge and understanding of feed nutrition causes the feed formulations not necessarily with feed standards (SNI) and feed commercial. Nutritious feed is essential for fish growth. The aim is to compare the nutrition of the tofu waste processed for local fish farmers, "Usaha Mandiri" in Tangkit Baru, with catfish feed standards and commercial. Fish feed produced by local fish farmers consists of 2 (two) types of pellets, it is pellet one consists of tofu waste and salted fish (50%:50%), and pellet two consists of a mixture of tofu waste, rice bran, and salted fish (30%: 20%: 50%). Measurement of feed nutrition includes crude protein (AOAC method, 2011); crude fat (SNI method 01-2891-1992); crude fiber (SNI method 01-2891-1992); ash content (AOAC method, 2005), and water content (AOAC method, 2005). The measurement results showed that the nutritional content in pellet one and pellet two, respectively, included crude protein (27.83%; 16.91%), crude fat (8.25%; 5.21%), crude fiber (5.71%; 5.49%), ash content (14.93%; 16.96%); and water content (29.59%; 26.23%). The nutritional content of pellet 1 was better than pellet 2, except for the ash content. The local pellet was by commercial feed and SNI 7548 (2009); pellet 1 is still feasible as an alternative feed for catfish farms.